Synchronization of the Fractional-Order Brushless DC Motors Chaotic System. (11th August 2016) - Shen, Shiyun; Zhou, Ping
Abstract : Based on the extension of Lyapunov direct method for nonlinear fractional-order systems, chaos synchronization for the fractional-order Brushless DC motors (BLDCM) is discussed. A chaos synchronization scheme is suggested. By means of Lyapunov candidate function, the theoretical proof of chaos synchronization is addressed. The numerical results show that the chaos synchronization scheme is valid.